Alendronic acid bearing acrylic monomer to produce heat resistant polyacrylonitrile copolymer and nanofibers - Yilmaz, Mustafa; Suer, N. Ceren; Eren, Tarik; Akar, Ahmet (TAYLOR & FRANCIS INC, 2021)
A new bisphosphonate-bearing acrylic monomer was synthesized with the Aza-Michael addition reaction from sodium alendronate and polyethylene glycol diacrylate. The PAN copolymer of the new monomer and acrylonitrile was heat resistant. In TGA analysis, the char yield of the copolymer at 650 degrees C was higher than that of PAN and the commercial poly(acrylonitrile-co-methyl acrylate) while poly(acrylonitrile-co-PEGDA-Ald) copolymers started to decompose at a lower temperature. T-g of the copolymers was considerably lower than PAN. Nanofibers were produced successfully by the electrospinning method from the mixture of poly(acrylonitrile-co-PEGDA-Ald) and poly(acrylonitrile-co-methyl acrylate). The poly(acrylonitrile-co-PEGDA-Ald) was also used to extract the copper ion from water.
Keywords: Flame-retardance; nanofiber; polyacrylonitrile; poly(ethylene glycol) diacrylate; alendronic acid; AZA-MICHAEL REACTION; FLAME RETARDANCY; BEHAVIORS; POLYMERS; FIBERS; Polymer Science